Nurse safety outcomes: old problem, new solution – the differentiating roles of nurses' psychological capital and managerial support. (24th June 2016) - Brunetto, Yvonne; Xerri, Matthew; Farr‐Wharton, Ben; Shacklock, Kate; Farr‐Wharton, Rod; Trinchero, Elisabetta
Abstract: Aim: The aim of this study was to examine the impacts of nurses' psychological capital and managerial support, plus specific safety interventions (managerial safety priorities, safety training satisfaction), on nurses' in‐role safety performance. Background: Most hospitals in industrialized countries have adopted selective (often the least costly) aspects of safety, usually related to safety policies. However, patient safety remains a challenge in many countries. Research shows that training can be used to upskill employees in psychological capital, with statistically significant organizational and employee benefits, but this area is under‐researched in nursing. Design: Data were collected using a survey‐based, self‐report strategy. The emerging patterns of data were then compared with the findings of previous research. Methods: Quantitative survey data were collected during 2014 from 242 nurses working in six Australian hospitals. Two models were tested and analysed using covariance‐based Structural Equation Modelling. Results: Psychological capital and safety training satisfaction were important predictors of nurses' in‐role safety performance and as predictors of nurses' perceptions of whether management implements what it espouses about safety ('managerial safety priorities'). Managerial support accounted for just under a third of psychological capital and together, psychological capital and managerial support, plus satisfaction with safety training, were important to nurses' perceptions of in‐role safety performance. Conclusion: Organizations are likely to benefit from upskilling nurses and their managers to increase nurses' psychological capital and managerial support, which then will enhance nurses' satisfaction with training and in‐role safety performance perceptions.